Improved network performance in CPS communication with distributed IPC mechanisms of recursive internetworking architecture (RINA). Issue 1 (21st March 2023) - Neelam, Bhushana Samyuel; Shimray, Benjamin A.
The network convenience provided by TCP/IP networks in Cyber-Physical Systems (CPS) communication redefined them as intelligent real-time systems. Along with convenience and intelligence, it also brought various network concerns into CPS communication. Some of the concerns include increased response times due to communication overheads, unnecessary delays in packet forwarding due to computational overheads, unwanted cyber threats in critical CPS infrastructures like energy, oil, gas, etc. As future networks are focused on achieving an optimum networking solution, Recursive Internetworking Architecture (RINA) based on distributed IPC mechanism seems to be a promising solution. The proposed work discussed extending distributed IPC mechanisms to the client-server communication model of CPS to extract improved and consistent response times compared to TCP/IP. A CPS client-server model is developed on RINA and TCP/IP networks with connection-oriented protocols. Response times are measured for controlling the actuators, sensing the sensors' data. The comparative analysis demonstrates that RINA reduced response times by almost 50% to TCP/IP and provided more consistency than the TCP/IP.